The trans DNA cleavage activity of Cas12a provides no detectable immunity against plasmid or phage - Liu, Shunhang; Rao, Xichen; Zhao, Ruiliang; Han, Wenyuan (Frontiers in Genome Editing, 2022)
Cas12a is a type V-A CRISPR-Cas RNA-guided endonuclease. It cleaves dsDNA at specific site, and then is activated for nonspecific ssDNA cleavage in trans in vitro. The immune function of the trans activity is still unknown. To address this question, we constructed a Cas12a targeting system in Escherichia coli, where Cas12a cleaved a high-copy target plasmid to unleash the trans ssDNA cleavage activity. Then, we analyzed the effect of the Cas12a targeting on a non-target plasmid and a ssDNA phage. The results show that Cas12a efficiently eliminates target plasmid but exerts no impact on the maintenance of the non-target plasmid or plague formation efficiency of the phage. In addition, a two-spacer CRISPR array, which facilitates target plasmid depletion, still has no detectable effect on the non-target plasmid or phage either. Together, the data suggest that the trans ssDNA cleavage of Cas12a does not contribute to immunity in vivo.